Pengembangan Joobsheet Pembelajaran Sistem Keamanan Jaringan pada Program Keahlian TKJ di SMK - Dwi Ratnawati; Sunarto Sunarto (Universitas Janabadra, 2016)
The study is categorized as research and development of research or research and development ( R & D ) . The research procedures used in concuting this study consist of some steps i.e.: information gathering, planning, early product development, product validation, revision, and product trials. At this stage of development jobsheet tested for feasibility by means of validation by experts (alpha test) , User jobsheet teachers and students as much as 2 consisted of 10 students (beta test) in Vocational High Scholl 1 Pleret, and then made the final revision . Next product assessment to determine the level of effectiveness of the use of jobsheet the way it is used directly in the learning in Vocational High Scholl 1 Pleret which 54 students . Data were analyzed with descriptive statistics only .The result of this research is a product jobsheet network security system that can be used by teachers and students in the learning process . Based on the results of the implementation of the beta test conducted in Vocational High Scholl 1 Pleret , product assessment results indicate that the product made has been met the needs of instructional media . This is indicated by the mean score of the overall assessment included in both categories . Keywords: Vocational High School , Jobsheet , Network Security System